FDP avulsion: A washer technique. (March 2021) - Weale, Ross; Atkinson, Richard; Muir, Lindsay
Abstract: Background: Flexor digitorum profundus (FDP) avulsion injuries occur following forced hyperextension of the distal interphalangeal joint (DIPJ). Methods: We highlight a case report of FDP avulsion injury fixed using a single hole of a plate in combination with a cortical screw to act as a washer. A search and discussion of the literature is included.